Preparation method of EBSD sample with cracks and characterization method of crack characteristics

By plating metal layers on the cracked cross-sectional samples and combining cold inlay, grinding, polishing and carbon spraying treatment, cracked EBSD samples with high resolution are prepared, which solves the problems of high production cost, low efficiency and low resolution in the prior art.

CN119619195APending Publication Date: 2025-03-14PIPECHINA SOUTH CHINA CO +2
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411589761.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art has high cost and low preparation efficiency in the process of preparing cracked EBSD samples, and the resolution rate of EBSD images is low.

Method used

By obtaining the cracked cross-sectional sample, the metal layer is coated on the fracture by electroplating, followed by cold inlay treatment, grinding treatment, at least two polishing treatments, cleaning treatments and surface carbon spraying treatments, to prepare cracked EBSD samples.

Benefits of technology

The resolution rate of EBSD images in typical areas of the primary and secondary cracks of the prepared EBSD sample with cracks is improved, the preparation cost is reduced, the preparation efficiency is improved, and the residual stress layer is effectively removed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119619195A_ABST
    Figure CN119619195A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an EBSD sample with cracks and a characterization method of crack characteristics, and relates to the technical field of preparation and testing of the EBSD sample with the cracks, and the method comprises the following steps: obtaining a fracture surface sample with the cracks; plating a metal layer on the fracture of the fracture surface sample with the cracks in an electroplating manner to obtain a plated fracture surface sample; and sequentially carrying out cold embedding treatment, grinding treatment, at least two times of polishing treatment, cleaning treatment and surface carbon spraying treatment on the plated section sample to prepare the EBSD sample with the cracks. The preparation process is simple, the preparation efficiency is high, the cost is low, and the analysis rate of EBSD images of typical areas of main cracks and secondary cracks of the prepared EBSD sample with cracks can be increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of EBSD sample preparation and testing with cracks, and in particular to a method for preparing an EBSD sample with cracks and a method for characterizing crack characteristics. Background Art

[0002] Electron backscatter diffraction (EBSD) is a technique that produces a Kikuchi diffraction pattern on the sample surface area by tilting the scanning electron microscope probe to deflect the electron beam at a certain angle (usually 70°C is the best), and then analyzes the crystal structure and orientation characteristics, dislocation density, high-angle grain boundary ratio and other information by calibrating the diffraction pattern. In the process of EBSD data collection, the state of the sample surface is a key factor, that is, the surface of the EBSD sample must be smooth, clean, and free of residual stress layers. However, the cost of preparing EBSD samples with cracks is currently high and the preparation efficiency is low. Summary of the invention

[0003] The technical problem to be solved by the present invention is to address the deficiencies of the prior art and specifically provide a method for preparing an EBSD sample with cracks and a method for characterizing crack characteristics, which are as follows:

[0004] 1) In the first aspect, the present invention provides a method for preparing an EBSD sample with cracks, and the specific technical scheme is as follows:

[0005] Obtain a cross-section specimen with a crack;

[0006] Plating a metal layer on the fracture surface of the cracked cross-section specimen by electroplating to obtain a plated cross-section specimen;

[0007] The plated cross-section sample is sequentially subjected to cold mounting treatment, grinding treatment, at least two polishing treatments, cleaning treatment and surface carbon spraying treatment to prepare an EBSD sample with cracks.

[0008] The beneficial effects of the method for preparing a cracked EBSD sample provided by the present invention are as follows:

[0009] On the one hand, by plating a metal layer on the fracture of the cracked cross-section sample, the resolution rate of the EBSD image of the main crack and the secondary crack typical area of ​​the prepared EBSD sample with crack can be improved; on the other hand, by grinding, at least two polishing and cleaning, the residual stress layer on the surface of the cracked cross-section sample can be effectively removed, and a good polishing effect is achieved, further improving the resolution rate of the EBSD image of the main crack and the secondary crack typical area of ​​the prepared EBSD sample with crack, and by cold mounting, the cross section can be protected and the situation of "the structure near the crack is affected by high temperature" can be avoided. The preparation process of the present invention is simple, the preparation efficiency is high, the cost is low, and the EBSD image of the cracked EBSD sample that can be prepared has a high resolution rate.

[0010] On the basis of the above scheme, the method for preparing a cracked EBSD sample of the present invention can be further improved as follows.

[0011] Further, a cross-section specimen with cracks is obtained, including:

[0012] By wire cutting, the cross-section specimen with cracks is cut out at the specified position of the fracture of the Charpy impact sample and along the notch and in the direction perpendicular to the cross section.

[0013] The beneficial effects of adopting the above further scheme are: on the one hand, the wire cutting method has the advantages of high efficiency and good precision; on the other hand, the wire cutting method will not have much impact on the components and structure near the crack and will not introduce impurities. Moreover, the wire cutting method is non-contact cutting, and the thermal deformation caused by wire cutting is small, which can prevent damage to the crack.

[0014] Furthermore, it also includes:

[0015] During the process of electroplating a metal layer on the fracture surface of a cracked cross-section specimen, the electroplating solution is kept in a flowing state.

[0016] The beneficial effect of adopting the above-mentioned further scheme is that in the process of electroplating a metal layer on the fracture surface of a cracked cross-section sample, the electroplating solution is kept in a flowing state, which can prevent the occurrence of "bubbles on the fracture surface of the cracked cross-section sample" and can quickly generate a metal layer, which can not only greatly shorten the electroplating time, but also effectively improve the quality of the metal layer.

[0017] Furthermore, the metal layer is a nickel layer, and the thickness of the nickel layer ranges from 20 μm to 30 μm.

[0018] Furthermore, the at least two polishing processes include: a mechanical polishing process and a vibration polishing process.

[0019] Furthermore, the method further comprises: mixing a transparent epoxy resin as a cold mounting agent with a curing agent and metal powder in a certain proportion to obtain a cold mounting material used in the cold mounting process.

[0020] The beneficial effect of adopting the above further solution is that the strength of the cold mounting material can be increased by adding metal powder.

[0021] Furthermore, the thickness of the carbon sprayed layer obtained by the surface carbon spraying treatment ranges from 10 to 30 nm.

[0022] The beneficial effect of adopting the above further scheme is: the cold mount material on the prepared cracked EBSD sample has good conductivity, which can improve the EBSD signal acquisition rate. If the carbon sprayed layer is too thin, electrons will be enriched and discharge will occur, affecting the collection of diffraction patterns; if the carbon sprayed layer is too thick, the backscattered electron signal will be weakened, reducing the recognition rate (resolution rate).

[0023] 2) In a second aspect, the present invention also provides an EBSD sample with a crack prepared by any of the above-mentioned methods for preparing an EBSD sample with a crack.

[0024] 3) In a third aspect, the present invention also provides a method for characterizing the crystallographic characteristics of crack extension, and the specific technical solution is as follows:

[0025] Performing EBSD testing on the main crack and the typical area of ​​the secondary crack of the EBSD sample with cracks prepared by any of the above-mentioned preparation methods for the EBSD sample with cracks to obtain EBSD data;

[0026] Preprocess EBSD data;

[0027] The preprocessed EBSD data are then processed to obtain the crack characteristic information of the main crack and the typical area of ​​the secondary crack of the EBSD sample with cracks.

[0028] The present invention also provides a method for characterizing crack extension crystallographic characteristics, which has the following beneficial effects:

[0029] By performing EBSD testing on the main crack and the typical area of ​​the secondary crack of the EBSD sample with cracks prepared by any of the above-mentioned preparation methods for the EBSD sample with cracks, the path of crack propagation and the crystallographic characteristics (i.e., crack characteristic information) can be observed more clearly, which is of great significance to the study of crack propagation.

[0030] On the basis of the above scheme, the characterization method of the crack extension crystallographic characteristics of the present invention can also be improved as follows.

[0031] Furthermore, the EBSD data is preprocessed, including: performing noise reduction processing on the EBSD data. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments of the present invention:

[0033] Figure 1 A schematic flow chart of a method for preparing an EBSD sample with cracks according to an embodiment of the present invention;

[0034] Figure 2 A schematic diagram of a process for combining a method for preparing an EBSD sample with a crack and a method for characterizing the crystallographic characteristics of crack extension according to an embodiment of the present invention;

[0035] Figure 3 It is a schematic diagram of cutting a cross-section specimen with cracks from a Charpy impact specimen by wire cutting;

[0036] Figure 4 It is a schematic diagram of the working principle of the electroplating device;

[0037] Figure 5 The morphology of the crack and nickel plating layer of the cross-section of the cracked cross-section specimen after nickel plating;

[0038] Figure 6 It is a schematic diagram of the structure of the plated cross-section sample after the fifth treatment;

[0039] Figure 7 An example of the process of obtaining an EBSD specimen with cracks in a Charpy impact sample;

[0040] Figure 8 Schematic diagram of fixing both the front and back sides of the cracked EBSD specimen to the sample stage;

[0041] Fig. 9 Schematic diagram of the EBSD characterization of the secondary crack cleavage propagation below the fracture surface. DETAILED DESCRIPTION

[0042] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0043] The technical solution of the present invention and how the technical solution of the present invention solves the above-mentioned technical problems are described in detail below with specific embodiments. The following specific embodiments can be combined with each other, and the same or similar concepts or processes may not be repeated in some embodiments. The embodiments of the present invention will be described below in conjunction with the accompanying drawings.

[0044] like Figure 1 As shown, a method for preparing an EBSD sample with a crack according to an embodiment of the present invention comprises the following steps:

[0045] S1. Obtain a cross-section specimen with a crack;

[0046] S2. electroplating a metal layer on the fracture surface of the cracked cross-section specimen to obtain a plated cross-section specimen;

[0047] S3. The plated cross-section sample is sequentially subjected to cold mounting treatment, grinding treatment, at least two polishing treatments, cleaning treatment and surface carbon spraying treatment to prepare an EBSD sample with cracks.

[0048] In a method for preparing a cracked EBSD sample according to an embodiment of the present invention, on the one hand, by plating a metal layer on the fracture of the cracked cross-section sample, the resolution of the EBSD image of the main crack and the secondary crack typical area of ​​the prepared EBSD sample with crack can be improved; on the other hand, by grinding, at least two polishing and cleaning, the residual stress layer on the surface of the cracked cross-section sample can be effectively removed, and a good polishing effect is achieved, further improving the resolution of the EBSD image of the main crack and the secondary crack typical area of ​​the prepared EBSD sample with crack, and by cold mounting, the cross section can be protected and the situation of "the structure near the crack is affected by high temperature" can be avoided. The present invention has a simple preparation process, high preparation efficiency, low cost, and the EBSD image of the cracked EBSD sample that can be prepared has a high resolution.

[0049] Optionally, in S1, obtaining a cross-section specimen with a crack includes:

[0050] By wire cutting, the cross-section specimen with cracks is cut out at the specified position of the fracture of the Charpy impact sample and along the notch and in the direction perpendicular to the cross section.

[0051] Among them, the wire cutting method has the advantages of high efficiency and good precision; the wire cutting method will not have much impact on the composition and structure near the crack and will not introduce impurities. Moreover, the wire cutting method is non-contact cutting, and the thermal deformation caused by wire cutting is small, which can prevent damage to the crack.

[0052] Optionally, it also includes:

[0053] In the process of electroplating a metal layer on the fracture surface of a cracked cross-section specimen, the electroplating solution is kept in a flowing state. This can prevent the occurrence of "bubbles on the fracture surface of the cracked cross-section specimen" and can quickly generate a metal layer, which can greatly shorten the electroplating time and effectively improve the quality of the metal layer.

[0054] Optionally, in the above technical solution, the metal layer is a nickel layer, and the thickness of the nickel layer ranges from 20 μm to 30 μm.

[0055] Optionally, in the above technical solution, the at least two polishing processes are: a mechanical polishing process and a vibration polishing process.

[0056] Optionally, the above technical solution also includes: mixing transparent epoxy resin as a cold mounting agent with a curing agent and metal powder in proportion to obtain a cold mounting material used for cold mounting treatment, and the strength of the cold mounting material can be increased by adding metal powder.

[0057] The metal powder is nickel powder or copper powder, which can be set according to actual conditions.

[0058] Optionally, in the above technical solution, the thickness of the carbon sprayed layer obtained by the surface carbon spraying treatment ranges from 10 to 30 nm.

[0059] The cold mounting material on the prepared cracked EBSD sample has good conductivity, which can improve the EBSD signal acquisition rate. If the carbon spray layer is too thin, electrons will be enriched and discharge will occur, affecting the collection of diffraction patterns; if the carbon spray layer is too thick, the backscattered electron signal will be weakened, reducing the recognition rate (resolution rate).

[0060] The present invention also provides an EBSD sample with cracks prepared by using any of the above methods for preparing an EBSD sample with cracks.

[0061] A method for characterizing crack extension crystallographic characteristics according to an embodiment of the present invention comprises the following steps:

[0062] S100, performing EBSD testing on the main crack and the typical area of ​​the secondary crack of the EBSD sample with cracks prepared by any of the above-mentioned preparation methods for the EBSD sample with cracks to obtain EBSD data;

[0063] S101, preprocessing EBSD data;

[0064] S102, and processing the preprocessed EBSD data to obtain crack characteristic information of the main crack and the secondary crack typical area of ​​the EBSD sample with cracks.

[0065] In a method for characterizing the crystallographic characteristics of crack propagation in an embodiment of the present invention, EBSD testing is performed on the main crack and the typical area of ​​the secondary crack of the EBSD sample with cracks prepared by any of the above-mentioned methods for preparing the EBSD sample with cracks, so that the path of the crack propagation and the crystallographic characteristics (i.e., crack characteristic information) can be observed more clearly. This is of great significance to the study of crack propagation.

[0066] Optionally, in S101, preprocessing the EBSD data includes: performing noise reduction processing on the EBSD data.

[0067] Through the following examples, Figure 2 As shown, the preparation method of the EBSD sample with cracks and the characterization method of the crack extension crystallographic characteristics of the present invention are described, including the following steps:

[0068] S201. Obtain a cross-section specimen with a crack.

[0069] According to the experimental requirements of EBSD, the cross-section specimen with cracks is cut out at the specified position of the fracture of the Charpy impact sample and along the notch and in the direction perpendicular to the cross-section by wire cutting. In order to completely characterize the nucleation, crack initiation and propagation path of the crack, the length of the cross-section specimen with cracks is preferably in the range of 8mm to 10mm, the width is in the range of 5mm to 10mm, and the height is in the range of 3mm to 5mm. The cross-section specimen with cracks is ultrasonically cleaned and then blown dry for storage.

[0070] like Figure 3 As shown, the cross-section specimen with cracks was cut along the notch and perpendicular to the cross-section in the middle of the fracture of the Charpy impact sample of X80 pipeline steel by wire cutting. The size of the cross-section specimen with cracks is 10 mm (length) × 10 mm (width) × 3 mm (height). Figure 3 In the figure, reference numeral 1 is the lower surface of the cross-section specimen with a crack, and reference numeral 2 is the upper surface of the cross-section specimen with a crack.

[0071] Among them, the wire cutting method has the advantages of high efficiency and good precision. The cutting accuracy can reach about 0.005mm. Moreover, the wire cutting method will not have much impact on the components and structure near the crack and will not introduce impurities. The wire cutting method is non-contact cutting, and the thermal deformation caused by wire cutting is small, which can prevent damage to the crack.

[0072] Among them, the material of the cracked cross-section specimen is low-carbon steel, low-alloy high-strength steel or stainless steel, and the crack characteristic data of the main crack near the cross-section and the secondary crack typical area below the main crack are used to characterize the crystallographic characteristics of crack propagation.

[0073] S202, performing nickel plating on the fracture surface of the cracked cross-section sample by electroplating to obtain a plated cross-section sample.

[0074] In order to ensure the resolution rate of the EBSD image of the main crack and the typical area of ​​the secondary crack below the main crack, it is necessary to plate a layer of nickel on the fracture surface of the cross-section specimen with cracks, that is, to plate a nickel layer on the fracture surface of the cross-section specimen with cracks. The thickness of the nickel layer is preferably in the range of 20μm to 30μm.

[0075] The specific implementation process of S202 is as follows:

[0076] First, the surface of the fracture of the cracked cross-section sample is cleaned, and it is rinsed by immersing in alcohol, dried and stored; secondly, the cleaned cracked cross-section sample is placed in the electroplating solution, and nickel is plated through the electroplating device, with the fracture as the cathode and the nickel plate as the anode. The electrochemical nickel plating process parameters are: temperature range of 40℃~60℃, time range of 15min~30min, current density of 4A / dm 2 ~6A / dm 2 During the nickel plating process, the plating solution is kept in a flowing state by means of magnetic stirring or manual stirring; finally, the nickel-plated cracked cross-section sample is taken out of the plating solution, immediately rinsed with clean water, and then ultrasonically cleaned for 3 to 8 minutes, and then dried and stored. Specifically, the cold air of a hair dryer can be used for drying.

[0077] Among them, the working principle of the electroplating device is as follows Figure 4 As shown, the break is connected to the cathode of the DC power supply, that is, the break serves as the cathode, and the nickel plate is connected to the anode of the DC power supply, that is, the nickel plate serves as the anode. The DC power supply of the electroplating device is also connected to a variable resistor to adjust the current, and is connected to an ammeter and a voltmeter to facilitate checking the current and voltage.

[0078] Among them, the crack morphology of the cross section of the cracked cross section specimen after nickel plating (the cross section at the end of the plated cross section specimen) is as follows: Figure 5 As shown, the nickel layer thickness is about 20 μm.

[0079] Among them, the use of magnetic stirring or manual stirring to make the plating solution in a flowing state can prevent the occurrence of "bubbles on the fracture of the cracked cross-section sample", and the direct current power supply electrolysis method can make nickel quickly deposited on the surface of the fracture of the cracked cross-section sample, which can not only greatly shorten the working time, but also effectively improve the quality of nickel plating. Under the same sample condition, the nickel plating method proposed by the present invention (which can be called the fracture fast nickel plating method) is 1h to 2h shorter than the traditional nickel plating method.

[0080] S203, sequentially performing cold mounting, grinding and mechanical polishing on the plated cross-section sample, specifically:

[0081] 1) The specific implementation process of cold mounting is as follows: First, make the height of the plated cross-section sample and the circular mold level, fix them on the glass plate, and fix the plated cross-section sample in the center of the circular mold; secondly, select epoxy resin as the cold mounting agent and mix it with the corresponding curing agent in a ratio that meets the requirements for the use of cold mounting materials. Add epoxy resin, dibutyl phthalate and ethylenediamine in a mixing ratio of 20:3:2 into a disposable plastic cup, and add 50% to 70% of the mass of the epoxy resin powder in copper powder or nickel powder and stir well, then let it stand for 10 to 15 minutes to obtain a cold mounting material; finally, slowly pour the cold mounting material into the circular mold and let it stand at room temperature for 10 to 12 hours to obtain the plated cross-section sample after the first treatment. The structure of the plated cross-section sample after the first treatment is as follows Figure 6 As shown, Figure 6 The EBSD scanning positions in the figure are typical areas of primary cracks and secondary cracks.

[0082] Among them, a transparent epoxy resin is used as a cold mounting agent and is mixed with a curing agent and metal powder (copper powder or nickel powder) in proportion to obtain a cold mounting material, which can protect the cross section. At the same time, an appropriate amount of copper powder or nickel powder can enhance the mounting strength and conductivity of the cold mounting material. In the present invention, it is not suitable to use the hot mounting method to mount the plated cross-section sample. The reason is that under the high temperature conditions (150-200°C) used in the hot mounting method, the structure near the crack may be affected.

[0083] Among them, the height of the circular mold used for cold mounting should be basically the same as the height of the coated cross-section sample. The circular mold should be fixed on the glass plate and compacted to prevent the cold mounting material from leaking from the bottom, and the coated cross-section sample should be fixed in the center of the circular mold. Then, the cold mounting material should be slowly poured into the circular plastic tube mold to ensure that no bubbles are incorporated, so that the cold mounting material can completely wrap the coated cross-section sample and fully ensure the integrity of the crack.

[0084] 2) The specific implementation process of the grinding treatment is: in the order of high to low particle size, select the corresponding sandpaper (such as silicon carbide water sandpaper, etc., which can be set according to the actual situation) to grind the plated cross-section sample after the first treatment. The particle size of the sandpaper used for grinding changes relatively slowly, and the particle size of the sandpaper used for grinding is relatively low, so that the organization and crystal structure near the crack can be more obvious after polishing. Specifically:

[0085] The plated cross-section sample after the first treatment is manually ground with sandpaper, and the particle size of the sandpaper used varies from 360 mesh to 5000 mesh, so that the height of the plated cross-section sample after the first treatment (the plated cross-section sample after the first treatment is recorded as the plated cross-section sample after the second treatment) is maintained within a suitable range, and preferably the height of the plated cross-section sample after the second treatment is 5 to 10 mm. The plated cross-section sample after the second treatment is rinsed with alcohol and blow-dried, and specifically, the cold air of a hair dryer can be used for drying.

[0086] 3) The specific implementation process of mechanical polishing is:

[0087] The surface of the plated cross-section sample after the second treatment was mechanically polished with a diamond polishing paste with an average particle size of 1.5 μm and a diamond polishing paste with an average particle size of 0.5 μm (also called a diamond grinding paste) in sequence to obtain a plated cross-section sample after the third treatment, specifically:

[0088] During polishing, a woolen fabric polishing cloth is used to polish the plated cross-section sample after the second treatment twice on a metallographic polishing machine at a speed of about 500rpm. First, a diamond polishing paste with an average particle size of 1.5μm is used to roughly polish the plated cross-section sample after the second treatment, which can remove the coarse scratches on the plated cross-section sample after the second treatment; then, a diamond polishing paste with a particle size of 0.5μm is used to finely polish the plated cross-section sample after the second treatment, which can remove the fine scratches on the plated cross-section sample after the second treatment. The mechanical polishing time should not exceed 15min to avoid destroying the corrosion product film of the plated cross-section sample after the second treatment. Before each polishing is completed, the polishing surface is rinsed with alcohol to wash away the polishing paste and polishing marks remaining on the polishing surface so as to more clearly observe the polishing effect, thereby obtaining the plated cross-section sample after the third treatment, and the plated cross-section sample after the third treatment is cleaned with alcohol, dried and stored, and can be dried with cold air from a hair dryer.

[0089] To a certain extent, mechanical polishing can reduce the thickness of the stress layer generated during the grinding process and improve the sample preparation efficiency of vibration polishing. The height range of the plated cross-section sample after the third treatment is preferably 5 to 10 mm. This height range can ensure: eliminating the crack tip that is slightly damaged when cutting the cross-section sample with a crack, thereby obtaining a complete crack propagation path; and can also ensure that the prepared EBSD sample with a crack will not accidentally collide with the probe of the EBSD testing device due to its excessive height.

[0090] S204, performing vibration polishing and ultrasonic cleaning on the plated cross-section sample after the third treatment, specifically:

[0091] 1) The specific implementation process of vibration polishing is: putting the plated cross-section sample after the third treatment into a vibration polishing machine for vibration polishing to obtain the plated cross-section sample after the fourth treatment. The vibration frequency of the vibration polishing machine is preferably in the range of 5000 to 8000 Hz. According to the material of the cross-section sample with cracks, an appropriate vibration polishing time is selected to ensure the effect of vibration polishing. Generally speaking, the vibration polishing time is usually in the range of 3h to 8h.

[0092] In another feasible method, the vibration frequency of the vibration polisher is set to between 5000 and 8000 Hz, and the plated cross-section sample after the third treatment is vibrated and polished for 2 to 3 hours, and then the surface vibration polishing effect is taken out and observed. If a micro-corrugated relaxation feature is present, it means that the vibration polishing effect is good; if no micro-corrugated relaxation feature is present, the vibration polishing time can be appropriately extended, generally not exceeding 8 hours. In addition, other appropriate vibration polishing working parameters can also be selected according to needs, which can be determined according to the sample.

[0093] 2) The specific implementation process of ultrasonic cleaning is: after the vibration polishing is completed, the suspension on the surface of the plated cross-section sample after the fourth treatment is rinsed with alcohol (the suspension is required during vibration polishing), and then immediately immersed in alcohol and ultrasonically cleaned for 5min to 10min to obtain the plated cross-section sample after the fifth treatment, and then the plated cross-section sample after the fifth treatment is blown dry and stored in a vacuum, wherein the cold air of a hair dryer can be used for drying.

[0094] In another achievable manner, after the vibration polishing is completed, the plated cross-section sample after the fourth treatment is immediately immersed in alcohol to prevent the suspension from drying on the surface of the plated cross-section sample after the fourth treatment. Thereafter, the plated cross-section sample after the fourth treatment is placed in an ultrasonic cleaning machine for cleaning to fully remove the residual suspension and impurities on the plated cross-section sample after the fourth treatment.

[0095] Electrolytic polishing is not suitable for the preparation of cracked EBSD samples, because the electrolyte solution ratio, voltage and current parameters required for electrolytic polishing are not fixed; ion polishing is only suitable for the preparation of small samples (generally less than 10 mm), and usually only has a good polishing effect on a small area in the center of the sample, which is not suitable for the preparation of cracked EBSD samples. Other sample preparation methods also have their own limitations for the preparation of cracked EBSD samples.

[0096] The advantages of vibration polishing are convenience and speed, but it has very high quality requirements for sample grinding and mechanical polishing; the amplitude, applied load and vibration time in the vibration polishing process will also vary with different materials, and there is no uniform standard requirement; the quality effect of vibration polishing is also judged based on experience.

[0097] S205, performing carbon spraying treatment on the surface of the plated cross-section sample after the fifth treatment to obtain an EBSD sample with cracks, that is, carbon is sprayed on the surface of the plated cross-section sample after the fifth treatment to obtain an EBSD sample with cracks. The structure of the EBSD sample with cracks is as follows: Figure 7 As shown, Figure 7 (a) Two cross sections obtained after Charpy impact and an example of brittle cracking sources; Figure 7 (b) An example of an EBSD specimen with a crack obtained by cutting section A along the brittle crack initiation source.

[0098] Among them, the thickness of the carbon sprayed layer is usually controlled between 10 and 30 nm, which can improve the conductivity of the cold-mounted material and the EBSD signal acquisition rate. If the carbon sprayed layer is too thin, it will affect the conductivity of the sample. In addition, electrons will be enriched in the plated cross-section sample after the fifth treatment and discharge will occur, affecting the collection of diffraction patterns. If the carbon sprayed layer is too thick, the backscattered electron signal will be weakened, which will have a greater impact on the resolution.

[0099] S206, performing EBSD testing on the main crack and the secondary crack typical area of ​​the prepared EBSD sample with cracks to obtain EBSD data, specifically:

[0100] like Figure 8 As shown in the figure, the surface and back of the EBSD sample with cracks are fixed to the sample stage with conductive glue, and the typical area of ​​crack extension (main crack and secondary crack typical area) is selected near the cross section for EBSD surface scanning to obtain crack extension related image data (such as Euler diagram, Kam diagram, etc.). The electron beam parameters are set according to the characteristics of the EBSD sample with cracks, and the scanning step length used in the EBSD test does not exceed 1 / 10 to 1 / 5 of the average grain size of the EBSD sample with cracks.

[0101] Among them, the surface and back of the cracked EBSD sample are fixed to the sample stage with conductive glue, which can enhance the conductivity of the cracked EBSD sample, thereby improving the scanning speed and signal quality of the EBSD test; then the cracked EBSD sample is placed in the sample chamber of the thermal field emission scanning electron microscope with conductive glue to obtain a clear EBSD image; the crystallographic structure existing in the matrix of the cracked EBSD sample is selected, and the working parameters of the EBSD test are set, specifically: the acceleration voltage working range is 20kV~25kV, and the probe current working range is 10nA~15nA. The specific working parameters of the EBSD test are generally selected according to the diffraction pattern signal quality of the cracked EBSD sample. Common working parameters for EBSD testing: acceleration voltage of 25kV, probe current of 15nA, characterized by "large current and large voltage", which can speed up the scanning speed of the cracked EBSD sample and also enhance the quality of the diffraction pattern signal. Select the analysis area and collect image data. The scanning step size was set to no more than 1 / 10 to 1 / 5 of the average grain size of the cracked EBSD specimen.

[0102] S207, pre-processing the acquired EBSD data, specifically:

[0103] The acquired EBSD data is subjected to noise reduction processing to obtain corrected EBSD data.

[0104] S208, processing the pre-processed EBSD data to obtain crack characteristic information of the main crack and the secondary crack typical area of ​​the EBSD sample with cracks, specifically:

[0105] The corrected EBSD data are processed and analyzed as needed, usually including the use of All-Euler+GrainBoundary diagrams to analyze the crack propagation surface and its relationship with the high-angle grain boundary, and the use of Band Contrast diagrams and KAM diagrams to qualitatively characterize the strain behavior around the crack. Fig. 9 (a) shows Fig. 9 (b) Scanned Euler diagram of secondary crack growth, Fig. 9 (b) In-situ scanning of the main crack and secondary crack. Fig. 9 (c) and Fig. 9 (d) Fig. 9 (b) In-situ SEM image of the secondary crack after enlargement.

[0106] At present, the resolution rate of EBSD images of cross-section samples with cracks is often low. Common reasons are generally rough surface, residual stress layer not removed, poor conductivity, etc. The fluctuation of composition and structure in the area near the crack will also affect the resolution rate of EBSD images. This usually requires that the polishing suspension ratio should not be too high, the amplitude of vibration polishing should not be too large, and the polishing time should not be too long, so as not to cause uneven composition and structure near the crack; usually, the residual stress generated near the crack is generally large, and the amplitude cannot be set too small, otherwise it will seriously affect the efficiency of vibration polishing to remove the residual stress layer on the surface of the sample. Under the condition of ensuring good conductivity of the sample surface, for the case of general resolution rate of sample EBSD images, the vibration polishing time can be appropriately increased to further remove the residual stress layer on the surface of the sample to try to improve the resolution rate of sample EBSD images; and for the case of low resolution rate of EBSD images due to poor quality of sample grinding or mechanical polishing, the sample can only be re-prepared.

[0107] That is to say, currently, it is very difficult to prepare EBSD samples with cracks and high resolution, and there are no clear vibration polishing process parameters. The present invention develops an efficient and stable method for preparing EBSD samples with cracks, which reduces the difficulty of preparing EBSD samples with cracks and high resolution, and is of great significance for studying the crystallographic characterization of crack propagation in metal materials.

[0108] The present invention improves the efficiency and success rate of EBSD technology in characterizing crack extension. In addition, by utilizing the existing crystallographic parameters during crack extension, a professional EBSD system is used to collect information such as crystal orientation and high-angle grain boundary ratio during crack extension, which is used to perform a series of qualitative / quantitative characterizations on the crack extension mechanism of the material, which is of great significance for studying crack extension. The economic cost spent in the sample preparation process of the present invention is low, and it is suitable for promotion and application. The present invention not only meets the requirements for EBSD sample detection with cracks, but also meets the microscopic observation of the morphology of the metal matrix below the cross section. Compared with the current crack extension characterization method, the present invention can more clearly observe the path and crystallographic characteristics of the crack extension.

[0109] In the above embodiments, although the steps are numbered S1, S2, etc., these are only specific embodiments given by the present invention. Those skilled in the art may adjust the execution order of S1, S2, etc. according to actual conditions, which is also within the protection scope of the present invention. It can be understood that in some embodiments, some or all of the above embodiments may be included.

[0110] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a cracked EBSD specimen, characterized in that: include: Obtain a cross-section specimen with a crack; Plating a metal layer on the fracture surface of the cracked cross-section specimen by electroplating to obtain a plated cross-section specimen; The plated cross-section sample is sequentially subjected to cold mounting treatment, grinding treatment, at least two polishing treatments, cleaning treatment and surface carbon spraying treatment to prepare an EBSD sample with cracks.

2. The method for preparing a cracked EBSD sample according to claim 1, characterized in that: The step of obtaining a cross-section specimen with cracks comprises: The cross-section specimen with cracks is cut out at a designated position of the fracture of the Charpy impact sample and along the notch and in a direction perpendicular to the cross section by using a wire cutting method.

3. The method for preparing a cracked EBSD sample according to claim 1, characterized in that: Also includes: During the process of electroplating the metal layer on the fracture surface of the cracked cross-section specimen, the electroplating solution is kept in a flowing state.

4. The method for preparing a cracked EBSD sample according to claim 3, characterized in that: The metal layer is a nickel layer, and the thickness of the nickel layer ranges from 20 μm to 30 μm.

5. The method for preparing a cracked EBSD sample according to claim 1, characterized in that: The at least two polishing processes are: mechanical polishing and vibration polishing.

6. The method for preparing a cracked EBSD sample according to claim 1, characterized in that: Also includes: The cold mounting material used in the cold mounting process is obtained by mixing a transparent epoxy resin as a cold mounting agent with a curing agent and metal powder in a certain proportion.

7. The method for preparing a cracked EBSD sample according to claim 1, characterized in that: The thickness of the carbon sprayed layer obtained by the surface carbon spraying treatment ranges from 10 to 30 nm.

8. An EBSD specimen with a crack prepared by the method for preparing an EBSD specimen with a crack according to any one of claims 1 to 7.

9. A method for characterizing the crystallographic characteristics of crack growth, characterized in that: include: Performing EBSD testing on the main crack and the typical area of ​​the secondary crack of the EBSD sample with cracks prepared by the method for preparing the EBSD sample with cracks according to any one of claims 1 to 7 to obtain EBSD data; Preprocessing the EBSD data; The pre-processed EBSD data is processed to obtain crack characteristic information of the main crack and the secondary crack typical area of ​​the cracked EBSD sample.

10. A method for characterizing crack extension crystallographic characteristics according to claim 9, characterized in that: Preprocessing the EBSD data includes: performing noise reduction processing on the EBSD data.

Citation Information

Cited By

  • Microscopic characterization method for deformation and dislocation density of metal material

    CN121275812A

  • FIB sample preparation method of electronic component mosaic sample for EBSD

    CN121347563A